MODIFIKASI PEMBELAJARAN DENGAN PERMAINAN TONNIS TERHADAP HASIL BELAJAR PUKULAN FOREHAND TENIS LAPANGAN (STUDI PADA SISWA PESERTA EKSTRAKURIKULER TENIS LAPANGAN SMAN 3 MOJOKERTO) - KHOIRIL ANWAR F N, M (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Forehand stroke is a matter that feels difficult for student. Many students that unable to perform those movement wehther on game nor when asked by teacher to practice it. One o fthe learning model is learning modification by tonnis game. Tonnis game played with similar way to tennis and suitable to become basic game before play field tennis. The aim of this reserarch was to detect : 1) the effect of field tennis learning modification by tonnis game to the forehand stroke learning result on student’s field tennis extracurricular participant of SMAN 3 Mojokerto. 2) The rate of tonnis modification to the forehand stroke learning result on student’s field tennis extracurricular participant of SMAN 3 Mojokerto. The conclusion of research result are : 1) there is significant effect from field tennis learning modification by tonnis game to the forehand stroke learning result on student’s field tennis extracurricular participant of SMAN 3 Mojokerto. It proved based on t test result namely tcount score 8.995 > ttable 2.045. 2) Learning modification by tonnis game give improvement to the forehand stroke learning result on student’s field tennis extracurricular participant of SMAN 3 Mojokerto as big as 22.65%. Keywords : modification, Tonnis learning result forehand, Field tennis.